2019
DOI: 10.1152/ajpendo.00243.2018
|View full text |Cite
|
Sign up to set email alerts
|

Intermuscular adipose tissue directly modulates skeletal muscle insulin sensitivity in humans

Abstract: Intermuscular adipose tissue (IMAT) is negatively related to insulin sensitivity, but a causal role of IMAT in the development of insulin resistance is unknown. IMAT was sampled in humans to test for the ability to induce insulin resistance in vitro and characterize gene expression to uncover how IMAT may promote skeletal muscle insulin resistance. Human primary muscle cells were incubated with conditioned media from IMAT, visceral (VAT), or subcutaneous adipose tissue (SAT) to evaluate changes in insulin sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
116
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(120 citation statements)
references
References 51 publications
2
116
2
Order By: Relevance
“…On the other hand, reduced SCFA production may trigger insulin resistance and result in increased fatty acid deposition within the muscle. The ensuing lower muscle quality may further promote insulin resistance, feeding a vicious circle that contributes to the onset and progression of PF&S [51,52]. Whether and how Ruminococcus and Oscillospira abundance impacts muscle metabolism and function in the context of PF&S warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, reduced SCFA production may trigger insulin resistance and result in increased fatty acid deposition within the muscle. The ensuing lower muscle quality may further promote insulin resistance, feeding a vicious circle that contributes to the onset and progression of PF&S [51,52]. Whether and how Ruminococcus and Oscillospira abundance impacts muscle metabolism and function in the context of PF&S warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Although not yet directly tested, the local accumulation of intermuscular adipose tissue may impair muscle metabolism by producing high intramuscular concentrations of adipokines, adipose-derived hormones, and free fatty acids. In support of this notion, some studies have reported positive correlations between intermuscular adipose tissue accumulation and the decrease in insulin sensitivity observed during aging and obesity (Goodpaster et al, 1997(Goodpaster et al, , 2000Ryan and Nicklas, 1999;Sachs et al, 2019). Interestingly, the majority of studies on intermuscular adipose tissue accumulation under conditions of metabolic stress have been conducted in humans.…”
Section: Connection Between Metabolic Stress and Ectopic Adipose Tissmentioning
confidence: 89%
“…Skeletal muscle, which is insulin sensitive, was shown to be found in larger quantities in the thigh compared with the abdomen . The location of IMAT next to skeletal muscle suggests a role for IMAT in insulin resistance; indeed, IMAT‐secreted factors were shown to reduce insulin sensitivity in myotubes in vitro , and thigh IMAT volume is positively associated with both insulin resistance and risk of T2D independent of overall obesity . There are also racial/ethnic differences in regional IMAT distribution, with studies reporting greater thigh and calf IMAT in African‐ancestry individuals compared with Caucasians , as opposed to similar or lower levels of abdominal IMAT.…”
Section: Introductionmentioning
confidence: 99%